Psychological traits of willingness to communicate: An assessment of students’ speaking performance - M Bambang Purwanto; Yuliana Yuliana; Habib Soleimani; Yusri Yusri (Universitas Aki, 2024)
This study explores the relationship between psychological traits and willingness to communicate (WTC) as well as the speaking performance of students in the Department of United Kingdom, Sriwijaya State Polytechnic. The psychological characteristics studied include self-confidence, anxiety about speaking, and motivation. A quantitative descriptive approach was used to collect and analyze data from a selected sample of students. The instruments used in this study include questionnaires to measure the level of confidence, speaking anxiety, and motivation and an assessment of speaking performance through a speaking test. The study's results showed a significant correlation between psychological traits and WTC and speaking performance. The calculation results show the Personality factor: Score 85, categorized as